Pelota-mediated ribosome-associated quality control counteracts aging and age-associated pathologies across species - Jongsun Lee; Bora Lee; Hyein Lee; Eun Ji E. Kim; Sieun S. Kim; Hyunwoo C. Kwon; Hanseul Lee; Gee-Yoon Lee; Woojin Hong; Seokjin Ham; Jae Won Yang; Heeju Park; et al. (Proceedings of the National Academy of Sciences, 2025)
Ribosome-associated quality control (RQC) is a pivotal biological process that governs the fidelity of messenger RNA (mRNA) homeostasis and protein synthesis. Defects in RQC are implicated in cellular dysfunction and proteotoxicity, but their impact on aging remains elusive. Here, we show that Pelota, the ribosome rescue factor, promotes longevity and protects against age-related pathological phenotypes in multiple metazoan species. By performing a targeted genetic screen, we find that Pelota is indispensable for longevity in the nematode Caenorhabditis elegans . We show that Pelota mitigates premature senescence in cultured human cells, muscle aging in mice, and neuropathology in cellular and organoid models of Alzheimer’s disease. Mechanistically, we demonstrate that Pelota maintains autophagy-mediated proteostasis, by preventing the hyperactivation of mechanistic target of rapamycin signaling. Overall, our work highlights the conserved functional significance of RQC, regulated by Pelota, in extending lifespan and protecting diverse species against age-associated disease phenotypes.